Medication use pattern and quality assessment of psychiatry outpatient department prescriptions of a tertiary care hospital - Pati, Ayan K.; Ghosh, Siddhartha (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Psychiatric illness is a major but often underreported health burden. The field of psychopharmacotherapy is continuously evolving therefore needs monitoring to prevent irrationality. In this setting, authors analyzed the prescribing pattern of psychotropic drugs while simultaneously monitoring prescription quality in a tertiary care teaching private hospital. Methods: A 6 month-prospective observational study was conducted in psychiatry out-patient department. Prescription pattern was analyzed using World Health Organization (WHO) drug use indicators. The quality of the prescriptions was assessed as per prescription writing guidelines issued by The Department of Health and Family Welfare, Government of West Bengal. Results: Of the 745 prescriptions analyzed, depression and psychosis constituted the bulk of diagnosed cases irrespective of any gender predominance. The average number of psychotropic drugs per prescription was 2.85±1.48. Antidepressants, sedative-hypnotic and anxiolytics are most commonly prescribed drugs. 37.58% of psychotropic drugs were given as fixed dose combination, most common being risperidone with trihexyphenidyl. Only 2.91% of the drugs were prescribed in generic name whereas 53.99% were enlisted in national essential medicine list 2015. Polypharmacy and therapeutic duplication were noted in 41% and 26.84 % of prescriptions and dose, duration and frequency were not mentioned in 2.68%, 53.02% and 19.00% of the prescription respectively. Conclusions: Use of psychotropic drugs follows closely with different treatment guideline, though routine uses of central anticholinergics with atypical antipsychotics are not recommended. Despite high utilization of NLEM, more generic prescribing, correct prescription dosing schedule, avoidance of polypharmacy and non-Judicious use of multivitamin FDCs may significantly improve treatment outcome.